2009
DOI: 10.18352/ijc.97
|View full text |Cite
|
Sign up to set email alerts
|

Payments for environmental services in upper-catchments of Vietnam: will it help the poorest?

Abstract: Abstract:In Asia, there is a surge of interest in the development of Payments for Environmental Services (PES) programs. They represent a new approach that focuses directly on creating a conditional benefit transfer between providers and beneficiaries of environmental services. More specifically, in Vietnam, a Fund for the Protection and Development of Forestry has been recently established that puts in place the mechanisms for the payment of fees by downstream users of watershed services to finance forestry p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Payment for environmental services (PES) schemes, whereby downstream residents compensate upstream land managers for their flood mitigation efforts, may be a promising tool for raising the motivation of farmers to establish soil conservation measures in sloping land (Neef and Thomas 2009). A study in northern Vietnam found that farmers are only likely to set land aside for conservation if they receive adequate in-kind compensation or productivity-enhancing technologies on their remaining farm area (Jourdain et al 2009). …”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Payment for environmental services (PES) schemes, whereby downstream residents compensate upstream land managers for their flood mitigation efforts, may be a promising tool for raising the motivation of farmers to establish soil conservation measures in sloping land (Neef and Thomas 2009). A study in northern Vietnam found that farmers are only likely to set land aside for conservation if they receive adequate in-kind compensation or productivity-enhancing technologies on their remaining farm area (Jourdain et al 2009). …”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…For small landholders, setting land aside means they reduce the already limited land they have available for food production and thus increase their food insecurity and financial instability (e.g. Jourdain et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, household-level opportunity costs and insecure land tenure often are cited as responsible for the limited success of the PFES program and other conservation efforts in some areas of Vietnam and other countries (Wunder 2008;Affholder et al 2010, McElwee 2012Jourdain et al 2014). Agriculture is the primary source of income in rural areas of Vietnam, and many households in upland areas have experience in crop production for subsistence or for sale in nearby markets (Jourdain et al 2009). The household-level benefits from crop production generally are larger than those available from protecting forest resources, particularly in the near term.…”
Section: Many Small Holdings and Low Payment Ratesmentioning
confidence: 99%